The Role of Labour Inspectorates in Tackling the Psychosocial Risks at Work in Europe: Problems and Perspectives - Dimitrios Toukas; Miltiadis Delichas; Chryssoula Toufekoula; Anastasia Spyrouli (Elsevier, 2015)
Significant changes in the past year have taken place in the world of work that are bringing new challenges with regard to employee safety and health. These changes have led to emerging psychosocial risks (PSRs) at work. The risks are primarily linked to how work is designed, organized, and managed, and to the economic and social frame of work. These factors have increased the level of work-related stress and can lead to serious deterioration in mental and physical health. In tackling PSRs, the European labor inspectorates can have an important role by enforcing preventive and/or corrective interventions in the content and context of work. However, to improve working conditions, unilateral interventions in the context and content of work are insufficient and require adopting a common strategy to tackle PSRs, based on a holistic approach. The implementation of a common strategy by the European Labor Inspectorate for tackling PSRs is restricted by the lack of a common legislative frame with regard to PSR evaluation and management, the different levels of labor inspectors' training, and the different levels of employees' and employers' health and safety culture.